Parametric algorithm for the automatic detection of artifacts in electroencephalography. - Muñoz Gamboa, C.; Saldivar Salazar, E. (Revista Mexicana de Ingenieria Biomedica, 1989)
The demonstration of the effectiveness of a detector algorithm of the artifacts that take place during the acquisition of the electroencephalogram (EEG) is presented. The algorithm is based on the separation of signals in two different regions of a parametric space, using a model that distinguishes non-polluting signals from those that contain artifacts. The advantages of the algorithm can detect and recognize the artifacts in real time, at the same time as they diagnose acquisition errors.